Radiative scattering in summer crop canopies (MAUSAM, 1985)
Scattering of radiation through crop canopies has been found to be linearly related over the entire to the foliage characteristics such as the foliage density and inclination index of foliage in the PAR range and by second degree regression in the NIR range. The scattering function presented higher cumulative values in the near infrared (NIR) as compared to the visible (PAR) range. The scattering was highly dependent on the crop geometry with higher amount of scattering in vertical inclined leaves and progressively decreased in crops with relatively horizontal 'nature of leaves.